Measuring the dynamic efficiency of socially responsible investment funds: evidence from dynamic network DEA with diversification. Issue 4 (1st December 2022) - Xiao, Helu; Liu, Xin; Ren, Tiantian; Zhou, Zhongbao
Abstract: This article proposes some alternative multi-period diversification-consistent data envelopment analysis (DEA) models to assess the dynamic performance of socially responsible investment (SRI) funds accounting for both finance and SRI criteria. First, three portfolio possibility sets (PPSs) are constructed based on some alternative dynamic input-output processes of SRI funds. Second, three diversification-consistent DEA models are developed by combining the directional distance function (DDF) measure with the proposed PPSs. Finally, this article selects 45 SRI funds to investigate the impact of social responsibility scores (SRSs), intermediate linkages, efficiency weights, and projection directions on their efficiency and ranking, respectively.